CONGENITAL KIDNEY AND URINARY TRACT ANOMALIES IN CHILDREN: EARLY DETECTION AND CLINICAL MANAGEMENT - Sobirjonov Javoxirbek Solijon oʻgʻli (Web of Journals Publishing, 2026)
Congenital anomalies of the kidney and urinary tract (CAKUT) account for 30-50% of pediatric end-stage renal disease and remain underdiagnosed in primary care settings. This prospective-retrospective study enrolled 247 children aged 0-14 years over five years. Prenatal detection was achieved in 63.2% of cases. Early intervention reduced surgical complication rates by 38.8% and significantly preserved long-term differential renal function.
Keywords: Hydronephrosis, vesicoureteral reflux, cakut, pyelectasis, pyelonephritis; nephrosonography, scintigraphy, urodynamics, obstructive uropathy, renal dysplasia, cystography, reflux nephropathy.